Training 21st century translators and interpreters : at the crossroads of practice, research and pedagogy. - Marc Orlando (Transkulturalität., 2016)
Long description: Marc Orlando looks at the gap between practice and research in Translation & Interpreting Studies and at the way this gap could be bridged. He focuses on the way practice and research can inform each other in the education and training of future translators and interpreters, with the aim of training future professionals both as practitioners and researchers in an educational environment that would marry both vocational and academic elements. It is proposed that promoting the status of practisearchers would help to fill the current gap between practitioners, researchers and Translation & Interpreting educators. Suggestions are made concerning ways of undertaking research and gaining new insights into Translation & Interpreting Studies from professional practice and experience, and of designing new didactic tools for education and training from experiential and theoretical knowledge.